Novel Application for Activated Carbon Pharmaceutical Formulation as an Efficient Adsorbent of Iron (III) from Contaminated Canned Food - Zahrah T. Althagafi; Hassan A. Arida; Reham F. Hassan (Journal of Chemistry)
Additional medical indication has been realized for the active carbon commercialized in pharmaceutical stores for the first time. In this study, the active carbon was used to remove iron (III) from real canned food samples contaminated with iron by an adsorption process, in a new approach. Different parameters affecting the adsorption behavior of active carbon towards iron (III) have been optimized. Under the optimized conditions, namely, pH 4, 5 h contact time, 40 ppm iron initial concentration, and 2 g carbon, the study was applied to some of the real canned food samples. Black olive and green bean canned food samples containing relatively high iron levels of 698.0 and 1168 mg kg-1, respectively, have been selected for this study due to their levels which were above the maximum permitted levels 48 mg kg-1 according to the Joint FAO/WHO Expert Committee on Food Additives (JECFA). These samples were digested and treated, and their iron concentration was determined using ICP-AES under the specified optimum conditions. The removal percentage of the real samples was ~91%. In a novel approach, this study simulates the adsorption behavior of active carbon towards iron (III) in the human stomach when canned food with relatively high iron levels has been digested, since the pH value of the human stomach (~3) comes in good agreement with the adsorption optimized pH range (2-4). Moreover, the overall tolerability and safety of active carbon are worldwide known and traditionally documented. These application studies realize the applicability of utilizing active carbon commercially available in pharmaceutical stores to eliminate the toxicity of canned food contaminated by high levels of the investigated elements.